Wear Behaviors of a Ti-Based Bulk Metallic Glass at Elevated Temperatures - Cao, Fuyang; Huang, Yongjiang; He, Chao; Fan, Hongbo; Wei, LiYuan; Ning, Zhiliang; Sun, Jianfei (Frontiers in Materials, 2021)
Bulk metallic glasses (BMGs) often offer excellent physical, chemical and mechanical properties like high strength, high hardness, and good wear/corrosion resistance, stemming from their unique atomic configuration. These properties enable them to be a potential engineering material in a range of industrial applications. However, the wear behaviors must be considered in structural applications. Here, the wear tests of a TiZrNiCuBe bulk metallic glass at high temperatures were carried out. As the testing temperature increases, the wear rate of the studied BMG sample gradually decreases and the sample surface becomes smoother. Meanwhile, a higher applied normal load causes a higher wear rate. The wear mechanism evolves from abrasive to adhesive mode with increasing the testing temperature. The results obtained here could shed more insights into the deformation mechanism of BMGs and thus extend their industrial uses in high temperature environments.